Evidence for an exercise induced increase of TNF-α and IL-6 in marathon runners - Bernecker, C.; Scherr, Johannes; Schinner, S.; Braun, S.; Scherbaum, W. A.; Halle, M. (Scandinavian journal of medicine & science in sports, 2013)
Regular physical activity of moderate intensity improves cardiovascular risk factors including low-grade inflammation. However, acute vigorous exercise such as marathon running results in marked increases of circulating pro-inflammatory markers. Up to now, the origin of this pro-inflammatory boost is still debated equivocally. We analyzed the change of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and leptin from pre- to immediately post-race in 15 male runners (age 43±10.9 years and body mass index 24.5±2.7kg/m2) both on the protein level in the plasma and on the messenger ribonucleic acid (mRNA) level in blood mononuclear cells (BMNC). We observed a significant increase of IL-6 (prerace 2.08±0.10ng/L and postrace 40.14±24.85ng/L, P<0.001) and TNF-α (prerace 8.14±1.38ng/L and postrace 12.40±3.15ng/L, P<0.001) and a decrease of leptin (prerace 1.64±2.64μg/L and postrace 0.80±1.70μg/L, P=0.04) serum levels after the marathon race. Furthermore, TNF-α, IL-6, and leptin were expressed (mRNA level) in BMNC. However no significant differences in mRNA levels were seen before and after the run in these cells. We found an up-regulation of TNF-α and IL-6 in the plasma during vigorous exercise. This increase is not attributable to BMNC. We assume a local production in, or release from, exercised tissues. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biomarkers; Cytokines; Exercise; Inflammation